Digital Twin for Metasurface Reflector Management in 6G Terahertz Communications - Pengnoo, Manus; Barros, Michael Taynnan; Wuttisittikulkij, Lunchakorn; Butler, Bernard; Davy, Alan; Balasubramaniam, Sasitharan (IEEE access, 2020)
The performance demands from data-intensive applications, such as multimedia streaming, as well as the growing number of devices connecting to the Internet, will increase the need for higher capacity wireless communication links. The research community has recently explored regions of the spectrum, including the Terahertz band (0.1 THz to 10 THz), that are underutilised for communications. THz frequencies come with a plethora of special challenges, one of which is the very narrow effective beam, thereby requiring a Line of Sight (LoS) between sender and receiver. Researchers have explored the use of reflectors that can redirect beams around blockages. In this paper, we propose a THz signal guidance system where a Digital Twin is used to model, predict and control the signal propagation characteristics of an indoor space. Our approach finds the best THz signal path from the base station to the mobile target via the tunable metamaterial walls, avoiding obstacles as needed, using geometric (ray tracing), path loss and Terahertz Potential Field (THzPF) models. With this knowledge, the digital twin guides the selection of antenna strips at a base station and the reflectors along the signal path. A top-view camera, with advanced image processing, provides context updates (obstacle and mobile target locations) to the digital twin. The image processing system also senses factors like water vapour concentration, and the material composition and surface roughness of obstacles. Such factors affect propagation strength, and the digital twin modifies the beam paths to adapt. Simulation results have shown the efficiency of our control system to maintain a reliable signal connection while minimising the use of antenna and reflector strips. Our system is the first proposal that maximises THz signal-to-noise ratio (SNR) through such a dynamic and robust control system, which integrates image processing of a room with base station configuration.